Effects of metformin on mitochondrial function of leukocytes from polycystic ovary syndrome patients with insulin resistance - Victor, Victor M; Rovira-Llopis, Susana; Bañuls, Celia; Diaz-Morales, Noelia; Castelló, Raquel; Falcón, Rosa; Gómez, Marcelino; Rocha, Milagros; Hernández-Mijares, Antonio (European journal of endocrinology, 2015)
ObjectiveOxidative stress and mitochondrial dysfunction are implicated in polycystic ovary syndrome (PCOS). The present study assesses the effect of metformin treatment on mitochondrial function in polymorphonuclear cells from PCOS subjects. Additionally, we evaluate endocrine parameters and levels of interleukin 6 (IL6) and tumour necrosis factor alpha (TNFα).Design and methodsOur study population was comprised of 35 women of reproductive age diagnosed with PCOS and treated with metformin for 12 weeks, and their corresponding controls (n=41), adjusted by age and BMI. We evaluated the alteration of endocrinological and anthropometrical parameters and androgen levels. Mitochondrial O2 consumption (using a Clark-type O2 electrode), membrane potential, mitochondrial mass, and levels of reactive oxygen species (ROS) and glutathione (GSH) (by means of fluorescence microscopy) were assessed in poymorphonuclear cells. H2O2 was evaluated with the Amplex RedR H2O2/Peroxidase Assay kit. IL6 and TNFα were measured using the Luminex 200 flow analyser system.ResultsMetformin had beneficial effects on patients by increasing mitochondrial O2 consumption, membrane potential, mitochondrial mass and glutathione levels, and by decreasing levels of reactive oxygen species and H2O2. In addition, metformin reduced glucose, follicle-stimulating hormone, IL6 and TNFα levels and increased dehydroepiandrosterone sulfate levels. HOMA-IR and mitochondrial function biomarkers positively correlated with ROS production (r=0.486, P=0.025), GSH content (r=0.710, P=0.049) and H2O2 (r=0.837, P=0.010), and negatively correlated with membrane potential (r=−0.829, P=0.011) at baseline. These differences disappeared after metformin treatment.ConclusionsOur results demonstrate the beneficial effects of metformin treatment on mitochondrial function in leukocytes of PCOS patients.